Bacillus subtilis Spore Resistance to Simulated Mars Surface Conditions - Cortesão, Marta; Fuchs, Felix M.; Commichau, Fabian M.; Eichenberger, Patrick; Schuerger, Andrew C.; Nicholson, Wayne L.; Setlow, Peter; Moeller, Ralf (Frontiers in Microbiology, 2019)
In a Mars exploration scenario, knowing if and how highly resistant Bacillus subtilis spores would survive on the Martian surface is crucial to design planetary protection measures and avoid false positives in life-detection experiments. Therefore, in this study a systematic screening was performed to determine whether B. subtilis spores could survive an average day on Mars. For that, spores from two comprehensive sets of isogenic B. subtilis mutant strains, defective in DNA protection or repair genes, were exposed to 24 h of simulated Martian atmospheric environment with or without 8 h of Martian UV radiation [M(+)UV and M(-)UV, respectively]. When exposed to M(+)UV, spore survival was dependent on (1) core dehydration maintenance, (2) protection of DNA by α/β-type small acid soluble proteins (SASP), and (3) removal and repair of the major UV photoproduct (SP) in spore DNA. In turn, when exposed to M(-)UV, spore survival was mainly dependent on (1) protection by the multilayered spore coat, and (2) repair of DNA double-strand breaks. Bacillus subtilis spores were able to survive for at least a limited time in a simulated Martian environment, both with or without solar UV radiation. Moreover, M(-)UV-treated spores exhibited survival rates significantly higher than the M(+)UV-treated spores. This suggests that on a real Martian surface, radiation shielding of spores (e.g., by dust, rocks, or spacecraft surface irregularities) might significantly extend survival rates. Thus, future efforts should focus on (1) determining the DNA damage in wild-type spores exposed to M(+/-)UV and (2) assessing spore survival and viability with shielding of spores via Mars regolith and other relevant materials.